Amniotic fluid Gram stain and interleukin‐6 can predict early‐onset neonatal sepsis. Issue 2 (9th December 2020) - Oshima, Yuko; Tanaka, Satoko; Tsumura, Keisuke; Tsuda, Satoko; So, Kunio; Shinagawa, Takaaki; Yamasaki, Fumio; Kawaguchi, Atsushi; Nomiyama, Makoto; Yokoyama, Masatoshi
Abstract: Aim: To clarify whether amniotic fluid findings (Gram stain and interleukin [IL]‐6 level) can predict early‐onset neonatal sepsis (EONS) before delivery. Methods: We compared the sensitivity and specificity and the values of the area under the receiver‐operating characteristic (AUROC) curve of maternal inflammatory responses and amniotic fluid findings using IL‐6 and Gram stain to predict EONS. Patients who underwent amniocentesis for suspected intra‐amniotic infection (IAI) after 22 weeks and 0 days of gestation and delivered on the same day at our hospital between January 2013 and December 2018 were included. Results: Out of 200 patients, EONS developed in 9 patients. The AUROC curves of maternal white blood cells count, C‐reactive protein and body temperature were low (range, 0.6–0.7), whereas that of amniotic fluid IL‐6 was high (0.90). Sensitivity and specificity for amniotic fluid findings were, respectively, 100% and 67% for IL‐6 (cut‐off value: 17.4 ng/mL) and 100% and 88% for the Gram stain; these values were superior to those of maternal inflammatory responses. When examining the accuracy of the amniotic fluid Gram stain separately before and after 34 gestation weeks, similar results were obtained. Amniotic fluid IL‐6 before 34 gestation weeks showed specificity similar to that of the Gram stain; however, there were large differences in cut‐off values based on gestational age. Conclusion: Gram stain results of amniotic fluid can predict EONS with high sensitivity and specificity when IAI is suspected. False‐negative amniotic fluid Gram stain results can be prevented by measuring amniotic fluid IL‐6 simultaneously.